PLP2 of mouse hepatitis virus A59 (MHV-A59) targets TBK1 to negatively regulate cellular type I interferon signaling pathway. - Gang Wang (Public Library of Science (PLoS), 2011)
Background Coronaviruses such as severe acute respiratory syndrome (SARS) coronavirus (SCoV) and mouse hepatitis virus A59 (MHV-A59) have evolved strategies to disable the innate immune system for productive replication and spread of infection. We have previously shown that papain-like protease domain 2 (PLP2), a catalytic domain of the nonstructural protein 3 (nsp3) of MHV-A59, encodes a deubiquitinase (DUB) and inactivates IFN regulatory factor 3 (IRF3) thereby the type I interferon (IFN) response. Principal findings Here we provide further evidence that PLP2 may also target TANK-binding kinase-1 (TBK1), the upstream kinase of IRF3 in the IFN signaling pathway. Overexpression experiments showed that PLP2 deubiquitinated TBK1 and reduced its kinase activity, hence inhibited IFN-β reporter activity. Albeit promiscuous in deubiquitinating cellular proteins, PLP2 inactivated TBK1 and IFN-β response in TNF receptor associated factor 3 (TRAF3) deficient cells, suggesting that targeting TBK1 would be sufficient for PLP2 to inhibit IRF3 activation. This notion was further supported by in vitro kinase assays, in which prior treatment of TBK1 with PLP2 inhibited its kinase activity to phosphorylate IRF3. Intriguing enough, results of PLP2 overexpression system and MHV-A59 infection system proved that PLP2 formed an inactive complex with TBK1 and IRF3 in the cytoplasm and the presence of PLP2 stabilized the hypo-phosphorylated IRF3-TBK1 complex in a dose-dependent manner. Conclusions These results suggest that PLP2 not only inactivates TBK1, but also prevents IRF3 nuclear translocation hence inhibits IFN transcription activation. Identification of the conserved DUB activity of PLP2 in suppression of IFN signaling would provide a useful clue to the development of therapeutics against coronaviruses infection.